1996
DOI: 10.1093/ajcn/64.3.436s
|View full text |Cite
|
Sign up to set email alerts
|

Why bioelectrical impedance analysis should be used for estimating adiposity

Abstract: The whole-body

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
209
2
21

Year Published

2000
2000
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 301 publications
(245 citation statements)
references
References 48 publications
7
209
2
21
Order By: Relevance
“…Another study in children with Prader Willi syndrome did find a similar regression coefficient (Davies, 1992). As can be seen from Figure 2 there is a lot of scatter around the line of best fit contributing to a high standard error of estimate Statement, 1994;Houtkooper et al, 1996) than have been observed in foot-to-foot BIA studies which may be of concern. A reason suggested by Nunez (1997) for the large SEE associated with body composition regression models in their studies was because of the diverse nature of the subject pool.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…Another study in children with Prader Willi syndrome did find a similar regression coefficient (Davies, 1992). As can be seen from Figure 2 there is a lot of scatter around the line of best fit contributing to a high standard error of estimate Statement, 1994;Houtkooper et al, 1996) than have been observed in foot-to-foot BIA studies which may be of concern. A reason suggested by Nunez (1997) for the large SEE associated with body composition regression models in their studies was because of the diverse nature of the subject pool.…”
Section: Discussionmentioning
confidence: 64%
“…Limitations associated with BIA technology include the assumption of constant hydration and FFM composition which can vary with obesity, disease, age and in different ethnic groups (Houtkooper et al, 1996). Although oedema was not observed in any of the subjects, some of them were receiving chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although bioelectrical impedance measurements capture body fat more accurately than anthropometric measurements,8, 38 they have limitations. Studies assessing bioelectrical impedance in diverse populations may require population‐specific calibration equations for different ethnic groups 8.…”
Section: Discussionmentioning
confidence: 99%
“…These reports were then stored in a protected electronic database with a patient identifier in order to retrospectively collect perioperative complication and outcomes data following surgery. It is important to note that PBF can be calculated through a variety of measures (hydrodensitometry, dual energy x-ray absorptiometry, anthropometric measures); however, body-fat estimation by current BIA has validated correlation against such measures [18][19][20].…”
Section: Obesity Classificationmentioning
confidence: 99%